Contributions of X (Formerly Twitter) in Sensitizing Nigeria Electorate Towards Exercising their Voting Rights in Presidential Elections - Okoli, Chizoba (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
The main aim of this study is to determine the role of twitter in sensitizing the Nigerian electorate towards exercising their voting right in Idemili North LGA of Anambra state. Survey research method was used in this study, the researchers found out that former twitter has a role in sensitizing Nigerian in the electorate towards exercising their right in Idemili North LGA. The researcher highlight the business-relationship-building-capacitate of former twitter as it enables customers and peers conversations that eventually support the development of products and service innovations. Again, former twitter has a capacity for marketers to inform and engage customers and peers in their networks on wider topics thereby building a brand of the individual users and their companies simultaneously. Finding, furthermore, former twitter enable quick way to distribute information, business intelligence and create a community. The study concludes that former twitter has become a tool to reach out to people of Idemili LGA in sensitizing them towards electoral processes. It recommends the combination of social media plate forms, like combining Whatsapp and Facebook in educating people towards their electoral obligations.